RURAL EDUCATION AND PUBLIC POLICIES: POPULAR KNOWLEDGE AND SOCIAL MOVEMENTS AS EXPRESSIONS OF STRUGGLE AND RESISTANCE - de Oliveira, Francisca Andreia Costa; de Lemos, Luiza Dayse Chaves; Pinheiro, Moisaniel Oliveira (Seven Editora, 2026)
Rural Education is a historical, political, and pedagogical construct woven from social movements led by peasant subjects seeking to guarantee rights, especially to an education designed for and with their people, based on territorial and cultural specificities, and guaranteeing access, quality, and permanence. This movement contributes to achievements legitimized in legal frameworks, the Public Policies for Rural Education. Thus, the objective was to analyze the relationship between Rural Education and educational public policies, highlighting how popular knowledge and the actions of social movements constitute expressions of struggle and resistance in the construction of counter-hegemonic educational practices committed to the emancipation of rural subjects. This research was developed through bibliographic and documentary investigation by means of a survey of related themes and the study of texts in: books, articles, dissertations, theses, digital platforms, and periodicals; as well as in current educational legislation. The main sources are: Arroyo (2006); Arroyo, Caldart and Molina (2004); LDB - Law No. 9.394/1996; CNE/CEB Resolution No. 1/2002; Coutinho (2009); Caldart (2004); Decree No. 7.352/2010; and Hage (2016). The results demonstrated that debating rural education in the sense proposed here requires recognizing that it is a political-pedagogical project in constant dispute, since it did not arise from a concession by the state, but from a historical process of struggles led by organized social movements that, in turn, pressured the transformation of collective demands into public policies. It is an expression of struggle and resistance that seeks to ensure the right to difference without relinquishing equality of rights. Therefore, it was concluded that Rural Education is not limited to a geographical space, but is configured as a permanent movement of resistance for the guarantee of rights and recognition of identity, since it has ensured the citizenship of rural populations, offering a teaching and learning process in accordance with the specificities of the countryside.